Activation of coagulation system and d-dimer levels in children with acute leukemia - Harun Wijaya; Novie Amelia Chozie; Badriul Hegar (Indonesian Pediatric Society, 2014)
Background D-dimer is a molecule as result of breaking downof excessive fibrin formation from the activation of coagulationsystem. There is evidence of increased activation of coagulation inpatients with acute leukemia which was showed by the incrementof d-dimer levels.Objective To evaluate the incidence of activation of coagulationsys tem in children with acute leukemia before receivingchemotherapy.Method This cross-sectional study was performed at Dr. CiptoMangunkusumo Hospital. All newly-diagnosed children with acuteleukemia were included in this study, prior to their receiving anychemotherapy treatment. Blast count, prothrombin time (PTI),activated partial thromboplastin time (APTf), and D-dimer levelswere examined after the diagnosis was confirmed by morphology andimmunophenotyping studies on bone marrow specimens.Results Out of 22 subjects, 13 subjects had increased D-dimervalues. The median D-dimer level of this elevated group was 1,000(range 500-14, 700) n gfmL. In the acute myeloblastic leukemia(AML) patients, activation of coagulation was found in 7 out of 8subjects. The median D-dimer levels was 950 (range 100-14, 700)ng/mL. In the acute lymphocytic leukemia (ALL) patients, 6 outof 14 subjects had increased activation of coagulation with medianD-dimer level of 300 (range 100-3,800) ngfmL. Nine out of 10subjects with blast cells on peripheral blood smear had a medianD-dimer level of 1,000 (range 500-3,800) ng/mL. Both PT andAPTT were found normal in all subjects.Conclusion Activation of coagulation sys tem occurs at thetime of diagnosis as shown by increased D-dimer levels. Thecharacteristics of activation of coagulation system are differentbetween ALL and AML subjects, as well as between subj ects withpositive and negative blast counts on peripheral blood smears.Despite the increased activation of coagulation, PT and APTfremain normal.